Mechanical strength of stock and custom abutments as original and aftermarket components after thermomechanical aging - Christiaan W. P. Pol; Marco S. Cune; Gerry M. Raghoebar; Lucas Z. Naves; Henny J. A. Meijer (Clinical and Experimental Dental Research, 2024)
Abstract Objectives The study aimed to assess the impact on the mechanical strength and failure patterns of implant‐abutment complexes of choosing different abutment types, designs and manufacturers, aiding in selecting the optimal restorative solution. Stock and custom abutments from original and aftermarket suppliers were subjected to thermomechanical aging. Material and Methods Stock and custom abutments from the implant manufacturer (original) and a aftermarket supplier (nonoriginal) were connected to identical implants with internal connection. Custom abutments were designed in a typical molar and premolar design, manufactured using the workflow from the respective suppliers. A total of 90 implants (4 mm diameter, 3.4 mm platform, 13 mm length) equally divided across 6 groups (three designs, two manufacturers) underwent thermo‐mechanical aging according to three different regimes, simulating five (n = 30) or 10 years (n = 30) of clinical function, or unaged control (n = 30). Subsequently, all samples were tested to failure. Results During aging, no failures occurred. The mean strength at failure was 1009N ± 171, showing significant differences between original and nonoriginal abutments overall (−230N ± 27.1, p < .001), and within each abutment type (p = .000), favoring original abutments. Aging did not significantly affect the failure load, while the type of abutment and manufacturer did, favoring original and custom‐designed abutments. The most common failure was implant bending or deformation, significantly differing between original and nonoriginal abutments and screws. All failure tests resulted in clinically unsalvageable implants and abutments. Conclusions Within the limitations of this study, original abutments exhibited a higher mechanical strength compared to the nonoriginal alternative, regardless of the amount of simulated clinical use. Similarly, custom abutments showed higher mechanical strength compared to stock abutments. However, mechanical strength in all abutments tested was higher than average chewing forces reported in literature, thus components tested in this study can be expected to perform equally well in clinical situations without excessive force.